“Reiterated Empathy” as Empathic Reverberation in Stein - Ivanoff-Sabogal, Christian (Anales del Seminario de Historia de la Filosofía, 2026)
In the phenomenological context intentionality makes a back-and-forth movement possible, since the ecstatic openness towards intentional correlates opens the way for their repercussion or reverberation in one’s own ‘subjectivity’ as the other pole of the intentional correlation. This paper deals with the phenomenon of reiterated empathy which appears briefly in Edith Stein’s On the Problem of Empathy and which we interpret in its specific manifestation as an empathetic reverberation. At first, the latent presence of different forms of a reverberating process is shown in Husserl, Scheler, Heidegger and Sartre, for whom reverberation always carries a negative feature. In a second step our aim is to prove that reiterated empathy and empathic reverberation fulfils, on the contrary, an essentially positive function according to Stein, because (a) they serve as a motivational genesis for inner perception and (b) they allow us to deepen our own self-knowledge and self-assessment. Keywords: phenomenology; inner perception; “interpersonality”; reverberation; self-deception. .
Keywords: phenomenology; inner perception; "interpersonality"; self-deception; reverberation